O valor do cliente e a escolha de ações na bolsa de valores - COELHO, Ricardo Limongi França (Universidade do Vale do Rio dos Sinos, 2010)
In this work I propose a tool that supports the investors trading decisions in the stock market, from a customer-based metric perspective.. This research is a case study that built on indicators often used by investors (and available through reports published by companies) and financial information published daily on the website of BM&FBOVESPA. Vale and Natura were chosen because they are in the Ibovespa and have different types of business relationships with their customers (contractual vs transitional). The dataset used includes the quarters between 2004 and 2009, totaling 20 observations. I found that customer equity contributes to the explanatory power of the stock price, and explored that fact tohelp decision makers
Keywords: Tomada de Decisão; Bolsa de Valores; Customer Equity; Decision Making; Stock Exchange; ACCNPQ::Ciências Sociais Aplicadas::Administração